(untitled) (Swiss Medical Weekly, 2022)
INTRODUCTION: Injuries are amongst the most frequent causes of morbidity and mortality worldwide. Our aim was to describe the frequency, type of injury and care provided in primary care in Switzerland. METHODS: We used anonymous data from 14,307 injury-related consultations of all ages, with a representative sample of 160 primary care physicians from the Sentinella network throughout the year 2017. Descriptive information about patients presenting with one or multiple injuries and the type of care provided were collected in a weekly questionnaire. Data about the primary care physicians including their experience, postgraduate training, equipment and skills were obtained using a single anonymous questionnaire. Negative binomial regression models with mixed effects were used to examine the association between primary care physicians’ characteristics, the proportion represented by injured patients in their total activity and independent management in primary care (without referral). With these models, the associations are expressed as a ratio of prevalence (PR). RESULTS: The median proportion (prevalence) of injury-related consultations was 2.0% (range 0.0–19.8%), with a significant difference between paediatricians and general practitioners (median 1.2% vs 2.1%). Nearly 60% of consultations for injuries involved men, 21.0% were for patients <18 years and 15.3% for those above 65. Sprains and dislocations (31.2%) were the most frequent diagnoses followed by cutaneous injuries (23.0%), contusions (20.1%) and fractures (18.8%). Of the injuries presenting directly to primary care, 87.0% were managed by the primary care physician without referral to external services. Fractures were the main diagnosis motivating referral, yet 67.9% of them were entirely managed within primary care. Multivariable analyses showed that training as a paediatrician and a longer experience in primary care were associated with having a lower prevalence of injury-related consultations (adjusted PR [adjPR] 0.49, 95% confidence interval [CI] 0.31–0.78 and adjPR 0.41, 95% CI 0.23–0.75, respectively), whereas the ability to offer wound care including sutures and both splints and casts were associated with a much higher prevalence of injury-related consultations (adjPR 9.36, 95% CI 3.42–25.61 and adjPR 2.38, 95% CI 1.43–3.97, respectively). CONCLUSION: The proportion represented by injured patients in a primary care physician’s total activity is heterogeneous. Most patients with mild to moderate injuries could be managed in primary care without referral to secondary care. Further studies could explore factors associated with patients’ decision to consult their primary care physician or emergency services for injuries. Exploring outcomes of primary care and patients’ satisfaction is another future research priority.